2015
DOI: 10.5194/isprsarchives-xl-7-w3-941-2015
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Multi-Year Synthetic Aperture Radar Imagery of Dry-Fallen Intertidal Flats

Abstract: ABSTRACT:We analyzed a great deal of high-resolution Synthetic Aperture Radar (SAR) data of dry-fallen intertidal flats in the German Wadden Sea with respect to the imaging of sediments, macrophytes, and mussels. TerraSAR-X and Radarsat-2 images of five test areas along the German North Sea coast acquired between 2008 and 2013 form the basis for the present investigation and are used to demonstrate that pairs of SAR images, if combined through basic algebraic operations, can already provide useful indicators f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Preferably, additional distinguishing characteristics are to be found to design a specific classification method, for example, by exploiting the polarized information of the SAR data. Various authors have shown the additional potential of multi-polarization SAR imagery for the detection of bivalve beds, using fully polarimetric e.g., [35,36] or dual-copolarized SAR data [37,38].…”
Section: Visual Analysis and Classificationmentioning
confidence: 99%
“…Preferably, additional distinguishing characteristics are to be found to design a specific classification method, for example, by exploiting the polarized information of the SAR data. Various authors have shown the additional potential of multi-polarization SAR imagery for the detection of bivalve beds, using fully polarimetric e.g., [35,36] or dual-copolarized SAR data [37,38].…”
Section: Visual Analysis and Classificationmentioning
confidence: 99%
“…Since it is increasingly exposed to anthropogenic threats such as (over-) fishing, high nutrient loads, oil and gas production, and tourism, its continuous monitoring is mandatory according to national and international directives [5,6]. However, most areas are difficult to access, hence in-situ observations are sparse, which makes remote sensing techniques important and powerful tools for the mapping of key parameters in such regions [7,8]. The strong dependence on sunlight and weather conditions always limits the usage of optical remote sensing sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The test site "Amrum" on the northern part of the German Wadden Sea (Figure 1) is located between the islands of Amrum and Föhr and was already subject to previous studies [11,12,27]. This region contains sandy and muddy sediments, vegetated areas, bivalve beds (mainly Pacific oysters and cockles, but also blue mussels) and seagrass meadows; hence it represents an area of a typical mixture of bivalve beds and sediments on exposed intertidal flats.…”
Section: Test Site and Sar Datamentioning
confidence: 99%